2017
DOI: 10.1289/ehp261
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Joint Effects of Early-Life Ambient PM2.5 Exposure and Maternal Prepregnancy Obesity on Childhood Overweight or Obesity

Abstract: Background:Although previous studies suggest that exposure to traffic-related pollution during childhood increases the risk of childhood overweight or obesity (COWO), the role of early life exposure to fine particulate matter (aerodynamic diameter <2.5μm; PM2.5) and its joint effect with the mother's prepregnancy body mass index (MPBMI) on COWO remain unclear.Objectives:The present study was conducted to examine the individual and joint effects of ambient PM2.5 exposures and MPBMI on the risk of COWO.Methods:W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 41 publications
(51 reference statements)
3
68
1
Order By: Relevance
“…Two duplicate studies conducted by the same lead authors using the same dataset were identified, one study was retained as environmental measures were included in the fully adjusted model, whereas they were not in the other study. In total, eight studies were included in the narrative synthesis . Four studies were based in the United States, one each in Canada, Denmark, England, and South Korea.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two duplicate studies conducted by the same lead authors using the same dataset were identified, one study was retained as environmental measures were included in the fully adjusted model, whereas they were not in the other study. In total, eight studies were included in the narrative synthesis . Four studies were based in the United States, one each in Canada, Denmark, England, and South Korea.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies recruited women during pregnancy, one study recruited shortly after birth, one study used a combination of the two, one study recruited 9 months after birth, and one study recruited children through schools . The recruitment rate varied between 12% and 78% (mean 51%) and was not presented in two studies . The percentage of the recruited sample who participated at each outcome time‐point varied between 22% and 83% (mean 60%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations